Studi Kepustakaan tentang Perkembangan Bahasa pada Anak Sekolah Dasar - ZD, Nadhifa Nur Rahmah; Wulandari, Tri; Isari, Alya; Kuntarto, Eko (Darul Yasin Al Sys, 2024)
The development of language in elementary school children is a crucial topic in the fields of education, developmental psychology, and linguistics. This research addresses significant gaps in understanding how social and educational environments influence language development in children. Using a literature review methodology, the study analyzes various factors affecting language acquisition, including the roles of family, school, and socio-economic status. Data were collected from relevant literature published within the last five years, focusing on the interaction between children and their teachers, peers, and parents. The findings reveal that effective teacher training significantly impacts children's language skills, highlighting the importance of interactive teaching methods. Additionally, children from higher socio-economic backgrounds tend to have better access to educational resources, which positively influences their language development. The results underscore the critical need for a supportive environment that fosters language growth through active engagement. In conclusion, this research contributes to the understanding of how various factors intertwine to shape language abilities in elementary school children, providing insights that can inform educational policies and practices aimed at enhancing literacy and communication skills in Indonesia.